Electroreductive cyclisation of unsatured halides catalysed by nickel macrocyclic complexes - Duñach, E. (1999)
The indirect electroreduction of unsaturated aliphatic halides using Ni(II) complexes as electron-transfer mediators is achieved in N,N'-dimethylformamide by constant current electrolysis between a cathode and a sacrificial anode in a diaphragmless cell. Cyclic compounds are obtained in low to high yields in conditions that avoid the usual preparation using organotin reagents.